Quantitative evaluation of policy texts of hospital workplace violence prevention and control in China: based on the PMC-Index model - Yuanshuo Ma; Yutong Huang; Xin Miao; Sulin Zhang; Jia Gao; Heyi Li; Meina Yuan; Jie Hu (BMC Public Health)
Abstract Background Workplace violence is one of the major public health problems in the world. In China, the problem of hospital workplace violence has been improved, but it remains significant. In order to prevent and punish such adverse events, China has introduced a series of policies and measures, however, there is still a lack of evaluative research on the effectiveness of these policies. Methods This paper, the PMC-Index model was used to establish a policy quantitative evaluation index system based on the high-frequency words in the policy texts in China. The consistency, advantages and disadvantages of 11 policies using a multi-input-output table. Results The policy evaluation system included 10 first-level variables and 52 second level variables. Of the 11 policies chosen, 5 exhibited good consistency (B), 6 showed acceptable consistency (C), and none were rated as poor. The average PMC-Index of B-level policies was 7.664, while for C-level policies it was 6.344. Overall, the level of all policies was deemed acceptable. Conclusions By constructing the PMC-Index model, it is evident that the overall design of hospital workplace violence policies in China is relatively rational, displaying a high standard and quality. Strengthening publicity and guidance, implementing coordination mechanisms between the police and medical, coordinating the cooperation of all social departments, and perfecting the construction of the legal system can be the main focus of policy improvement and optimization in the future.